The monitoring technology to asses of professional masters teachers of music (Pedagogy of Higher and Secondary Education, 2006)
The article cavers the essence of monitoring evaluation technology of future teachers of music professional stall as of modernized quality education control. Special attention is drawn to the informal aspects of the monitoring functions and their classification.
Keywords: monitoring; technology; professional masters; to asses; teachers of music